The Abolition of the Presidential Threshold and the Reconstruction of Presidential Nominations: A Political-Legal, Political Economy, and Siyāsah Dustūriyyah Analysis - Umarwan Sutopo; Muhammad Ali Murtadlo; Hilman Rosyidi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The Constitutional Court's Decision Number 62/PUU-XXII/2024, which abolishes the presidential threshold, marks an important change in the presidential nomination system in Indonesia. This research aims to analyze the legal-political construction underlying the abolition of the presidential threshold, examine its implications for the political economy structure of elections, and formulate a presidential nomination model that reflects the perspective of siyāsah dustūriyyah. This research is a normative legal study using the statute approach, case approach, conceptual approach, and Islamic legal approach. Data was obtained through library research on legislation, Constitutional Court decisions, and related literature and then analyzed qualitatively. The research results indicate that the removal of the presidential threshold reflects a shift in legal politics from an orientation toward political stability to the strengthening of people's sovereignty, equality of political rights, and a more inclusive democracy. From a political economy perspective, the policy expands political competition and strengthens the opportunities for medium and small parties, but it also has the potential to give rise to new forms of oligarchic dominance through political funding and high campaign costs. From the perspective of siyāsah dustūriyyah, this research offers a model of presidential nomination based on justice and public interest, grounded in open nominations, internal party democracy, political funding reform, equal access to campaigns, and program-based coalition governance to achieve political justice, public welfare, and government stability.